Fabrication of Zr-based bulk metallic glass/aluminum alloy multi-materials by stacking extrusion. (March 2018) - Jiang, Rui; Li, Huiping; Li, Zhichao; He, Lianfang
Abstract: Zr-based bulk metallic glass(BMG)/7075 aluminum alloy multi-materials have been successfully fabricated by extrusion in the vertical stacking form. Extrusion tests were carried out at 713 K within the supercooled liquid region(SLR) and the ram speed of 2 mm/min. An interface of which Al alloy is inserted into BMG and wrapped tightly by BMG in the periphery is obtained. The interface between BMG and Al alloy has been characterized by a variety of techniques including Optical Microscope (OM), Scanning Electron Microscope(SEM), X-ray diffraction(XRD) and Transmission Electron Microscope(TEM). The interface is estimated to be defect-free. BMG matrix maintains well amorphous with only a small quantity of nanocrystals at the interface, and elements diffusion is also detected. Both the macrostructure and microstructure analyses indicate a good bonding between dissimilar materials at the interface. Highlights: A method of co-extrusion in the vertical stacking form is proposed. The interface between BMG and Al alloy is found to be a new form with cladding. The BMG matrix maintains well amorphous with only few nanocrystals at interface. Metallurgical bonding is formed between BMG and Al alloy.